(untitled) (Bangladesh Journal of Medical Science, 2019)
The trend of NCDs in most LMIC countries is slowly but gradually follows that of in the developed countries. There are four significant diseases reported by WHO, which are equally common, such as CVDs, diabetes, cancer, and chronic respiratory disease that causes widespread early death & morbidity. Indeed, it incurs an overwhelming financial burden to most countries in the world. The rise of drug-resistant microbes is another major problem. To overcome this issue, precision medicine (PM) comes into play whereby individual variability in genes, environment, lifestyle, and nutrition of each person is considered for disease treatment & prevention. PM provides a personalized approach, the right treatment to the right people at the right time. Many wealthy countries in the West have started adopting PM though the initial cost is high, ultimately, in the long run, will reduce the healthcare cost by getting rid of the ineffective treatment strategies. However, the PM in LMICs is still at an early stage due to issues such as lack of populationspecific data, competency, expertise, and poor financial support. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.32-47